A Narrative of the Expedition to Botany-Bay - Tench, Watkin, 1759?-1833 (Salt Lake City, UT : Project Gutenberg, 2006)
"A Narrative of the Expedition to Botany Bay" by Watkin Tench is a historical account written in the late 18th century. The book recounts the experiences of Tench, a Captain of the Marines, during the British expedition that led to the establishment of a penal colony in Australia at Botany Bay. It not only details the journey of convicts and soldiers from England to their new settlement but also reflects upon the observations made about the indigenous people and the environment of this new land. The opening of the narrative introduces the voyage, commencing with the preparations and embarkation of convicts and marines from various ports in England. Tench provides insights into the moods of the convicts, their behavior on the ships, and the challenges faced during the journey, including maintaining order among the prisoners while dealing with an atmosphere of anticipation and impending change. As the expedition progresses, Tench carefully documents the interactions with the convicts and comments on their resilience and hope as they sail toward an uncertain future in a distant territory. The narrative sets the stage for a deeper exploration of the difficulties and adaptations that would follow upon their arrival. (This is an automatically generated summary.)
Release date is 2006-05-08
Produced by Col Choat and Stuart Kidd
Keywords: Voyages and travels; Tench, Watkin, 1759?-1833 -- Diaries; Explorers -- Australia -- New South Wales -- Diaries; Botany Bay region (Australia) -- Description and travel; New South Wales -- Description and travel; Australia -- Discovery and exploration